Proposal of a web application for monitoring the impact of news on Facebook and Twitter social networks - Leite, Nelson (2013)
This paper summarizes the main results of a research project which main goal was the design, development and evaluation of a web application for monitoring the buzz of news and other contents published in social networks (Facebook and Twitter) by the online news portal of the University of Aveiro. With this application a wiser decision making process can be achieved on the management of the publishing cycle of the news portal.